Enhancing eyes-free interaction in virtual reality using sonification for multiple object selection - Takahara, Yota; Niijima, Arinobu; Park, Chanho; Ogawa, Takefumi (Frontiers in Virtual Reality, 2025)
In virtual reality (VR) environments, selecting and manipulating multiple out-of-view objects is often challenging because most current VR systems lack integrated haptics. To address this limitation, we propose a sonification method that guides users’ hands to target objects outside their field of view by assigning distinct auditory parameters (pan, frequency, and amplitude) to the three spatial axes. These parameters are discretized into three exponential steps within a comfortable volume (less than 43 dB) and frequency range (150–700 Hz), determined via pilot studies to avoid listener fatigue. Our method dynamically shifts the sound source location depending on the density of the target objects: when objects are sparsely positioned, each object serves as its own sound source, whereas for dense clusters, a single sound source is placed at the cluster’s center to prevent overlapping sounds. We validated our technique through user studies involving two VR applications: a shooting game that requires rapid weapon selection and a 3D cube keyboard for text entry. Compared to a no-sound baseline, our sonification significantly improved positional accuracy in eyes-free selection tasks. In the shooting game, participants could more easily swap weapons without losing sight of on-screen action, while in the keyboard task, typing accuracy more than doubled during blind entry. These findings suggest that sonification can substantially enhance eyes-free interaction in VR without relying on haptic or visual cues, thereby offering a promising avenue for more efficient and comfortable VR experiences.